Vinum laetificat cor hominis (Ps 104,15). Ojcowie Kościoła o spożywaniu wina i związanych z tym problemach - Wygralak, Paweł (Poznańskie Studia Teologiczne, 2011)
The article deals with the teaching of the Church Fathers on the consumption of wine and the ensuing problems. From an analysis of the statements of ancient authors it follows that they were not absolute enemies of wine drinking and claimed that as God’s gift wine could give people joy and warm up the organism. It can therefore without much fear be drunk by the elderly whose desires are curbed by age and reason. The young, however, should be aware of the many dangers entailed by the abuse of alcohol. Drunkenness, according to the teaching of St. Paul, is classified as grave sin. In the opinion of the Fathers drunkards cannot control their emotions and passions and this leads them to neglect their families and draw away from God. For this reason ancient preachers address those who abuse alcohol with words of encouragement to take up struggle against the addiction and in this way take care of the salvation of their souls. In their efforts to free themselves from their addiction they should be supported by those closest to them.